1999
DOI: 10.1021/la980668f
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Silica Nanoparticle Adsorption Using Optical Reflectometry and Streaming Potential Techniques

Abstract: The kinetics of adsorption of monodisperse nanosized silica particles (32−190 nm diameter) on silicon wafers modified with an aminopropylsilane have been studied by optical reflectometry under stagnant-flow conditions. The adsorption of negatively charged particles on a positively charged wafer surface is driven by electrical double layer attraction and was not found to be measurably reversible. The initial rate of particle adsorption decreases with increasing particle size while the equilibrium amount adsorbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
46
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 17 publications
6
46
0
Order By: Relevance
“…The initial deposition rate increased with decreasing particle size and increasing particle concentration [19,20]. They also showed that while the deposited amount of nanoparticles and surface coverage increased with increasing concentration of NaCl, the initial deposition rate remained unaffected [19,20].…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…The initial deposition rate increased with decreasing particle size and increasing particle concentration [19,20]. They also showed that while the deposited amount of nanoparticles and surface coverage increased with increasing concentration of NaCl, the initial deposition rate remained unaffected [19,20].…”
Section: Introductionmentioning
confidence: 96%
“…The deposition of nanoparticles can also be studied by optical reflectometry (OR) [16,[18][19][20][21] where the reflecting substrate carries a thin dielectric layer [22]. Böhmer et al used OR to study how the size and concentration of silica nanoparticles and the ionic strength affected the deposition onto polyelectrolyte-coated substrates [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…15,16 In this technique the surface's electrokinetic properties are altered by introducing a heterogeneous region, for example due to protein adsorption, which has a different -potential than the original surface. The introduction of this heterogeneous region induces a change in the surface's average -potential, which is monitored via a streaming potential measurement, and related back to the degree of surface coverage.…”
Section: Introductionmentioning
confidence: 99%